Comparative analysis of korean imitative words with imitative words in kazakh language. - Shatekova., G. K. (Journal of Oriental Studies, 2016)
In article the author, describing and comparing imitative words of the Korean and Kazakh languages, analyzes them. As a result of research, having compared and having connected words of two languages, the author shows their similarities and differences.